Anisotropy of Fatigue Behavior and Tensile Behavior of 5A06 Aluminum Alloy Based on Infrared Thermography - 闫志峰 张红霞 CHEN Pengda WANG Wenxian (Journal of Wuhan University of Technology. Materials science edition, 2017)
The fatigue behavior during high cycle fatigue testing and the tensile behavior of 5A06 aluminum alloy considering the anisotropy were studied.Two types of specimens including longitudinal specimen（parallel to the rolling direction） and transverse specimen（perpendicular to the rolling direction） were prepared.Infrared thermography was employed to monitor the temperature evolution during the fatigue and tensile tests.The temperature evolution curves in the two directions were contrastively analyzed.It is found that the temperature evolution during fatigue process possesses four stages：initial temperature rise stage,slow temperature decline stage,rapid temperature rise stage,and finial temperature decline stage.The heat generating mechanisms of the four stages are discussed.Obvious differences can be found between the longitudinal specimen and transverse specimen in fatigue strength and fatigue life.The fatigue strength and fatigue life of longitudinal specimen are higher than those of transverse specimen.During the tensile and fatigue testing process,the fracture temperature in the transverse direction are higher than that in the longitudinal direction.The fatigue strength prediction by means of infrared thermography has a good consistency with that by the traditional method.